Efficacy of Oral Carvedilol Premedication in Attenuating the Hemodynamic Response to Direct Laryngoscopy and Endotracheal Intubation - Koirala, Siddhartha; Dhakal, Yogesh; Baral, Sameep Raj; Ghimire, Ashish (Birat Journal of Health Sciences, 2020)
Introduction: Laryngoscopy and endotracheal intubation is associated with significant hemodynamic changes. Though these changes are well tolerated in healthy patients, they are undesirable in patients with comorbidities like coronary artery disease, systemic hypertension, myocardial insufficiency and intracranial hypertension. Various drugs have been tried in an effort to attenuate adverse hemodynamic responses to intubation, but so far none is ideal. Objectives: To find efficacy of low dose oral carvedilol in attenuating the hemodynamic responses to direct laryngoscopy and endotracheal intubation. Methodology: In this randomized, prospective, double-blind placebocontrolled study 80 patients of either sex aged between 18 and 60 years of age, belonging to the American Society of Anesthesiologists (ASA) health status Classes I and II, undergoing elective surgery requiring general anesthesia with endotracheal intubation were included. Patients were randomly divided into two groups. Group A: given 3.125 mg of Carvedilol orally and Group B: given a placebo (Vitamin B capsule) orally one hour before intubation with sips of water. Hemodynamic parameters were noted before and then 1, 2, 5, 10, 15 min after intubation. Any adverse effects associated with drugs were noted. Results: Both groups were well matched for their demographic data. There was a statistically significant difference (P< 0.05) between carvedilol and placebo in heart rate at all points of measurement after tracheal intubation. The systolic blood pressure was significantly lower in carvedilol group only at 5min after intubation. Diastolic and mean blood pressures were comparable in every points of measurement. None of the patients had any adverse effects. Conclusion: Low dose carvedilol has statistically significant effect in attenuating the heart rate response to direct laryngoscopy and endotracheal intubation.